ANALYSIS OF THE MEDICAL DATA STRUCTURE USING SELFORGANISING MAPS - Hodych, O. V.; Nikolsky, Yu. V.; Pasichnyk, V. V.; Scherbyna, Yu.Scherbyna M. (International Journal of Computing, 2014)
In this article the authors discuss several approaches to high dimensional data structure analysis using Self- Organising Maps. The describe approaches utilise graphical images for the purpose of data structure interpretation. The evaluation of the discussed techniques has been performed using the real medical data from cardiology. The research, results of which are outlined in this paper, is a continuation of the earlier work related to the analysis of the same medical data. It is envisaged that results obtained in this and earlier research work will form a foundation for creation of a robust technology to be used for automation of diagnostic tasks in medicine.